Localising the Global Qirāʾat Tradition in the Nusantara: A Philological Study of Hasyim Jakfar's Quflul Qirāʾat - Ridhoul Wahidi; Riki Rahman; Daing Mohd Fuad a Kadir Tawajok; Dadang Darmawan; khairul Ihsan (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
Locally produced qirāʾat manuscripts in the Malay Archipelago remain critically underexplored despite their significance in regional Islamic pedagogy. This article examines Quflul Qirāʾat Baina Imāmaini (QQBI), an unpublished Jawī-script manuscript by Hasyim Jakfar (1945–2022) of Indragiri Hilir, Riau, Indonesia. Employing a qualitative philological-hermeneutical design, the study analyses both external (mā ḥaula al-kitāb) and internal (mā fī al-kitāb) dimensions using Islah Gusmian's Nusantara manuscript framework, supplemented by content analysis and interpretive hermeneutics. The findings reveal that QQBI systematically juxtaposes the recitational systems of Imām Nāfiʿ (via Qālūn and Warsh) and Imām Ibn Kathīr (via Qunbul and al-Bazzī), identifying four structural convergences and fifteen methodological divergences across two parallel sections. Adopting a sharḥī presentational format, the manuscript provides an inclusive pedagogical orientation for Musabaqah Tilāwatil Qurʾān (MTQ) participants, regardless of prior tajwīd mastery. While QQBI successfully localises the classical Shāṭibiyyah tradition into an accessible instructional framework, its absence of explicit taḥqīq and isnād documentation constitutes a critical methodological limitation. This study argues that QQBI represents a productive yet incomplete model of qirāʾat knowledge localisation, with broader implications for Islamic manuscript scholarship and qirāʾat pedagogy in Southeast Asia.